Online education : foundations, planning, and pedagogy - Picciano, Anthony G. (New York : Routledge, 2019)
Online Education is a comprehensive exploration of blended and fully online teaching platforms, addressing history, theory, research, planning, and practice. As colleges, universities, and schools around the world adopt large-scale technologies and traditional class models shift into seamless, digitally interactive environments, critical insights are needed into the implications for administration and pedagogy. Written by a major contributor to the field, this book contextualizes online education in the past and present before analyzing its fundamental changes to instruction, program integration, social interaction, content construction, networked media, policy, and more. A provocative concluding chapter speculates on the future of education as the sector becomes increasingly dependent on learning technologies.
Chapter 1. Introduction to foundations, planning, and pedagogy -- Section 1. Foundations -- Chapter 2. The history and evolution of online education -- Chapter 3. Theoretical frameworks for online education: Seeking an integrated model -- Chapter 4. Research on online education -- Section 2. Planning and Pedagogy -- Chapter 5. Planning for online education: A systems model -- Chapter 6. Designing instruction for online environments -- Chapter 7. Academic, administrative and student support structures -- Chapter 8. Navigating the current landscape -- Blending it all together! -- Chapter 9. The 2020s, 2030s, and beyond!
Includes bibliographical references and index.
Keywords: Web-based instruction; Distance education -- Effect of technological innovations on